2012
DOI: 10.1186/1297-9716-43-49
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipooligosaccharide phosphorylcholine in colonization and pathogenesis of Histophilus somni in cattle

Abstract: Histophilus somni is a Gram-negative bacterium and member of the Pasteurellaceae that is responsible for respiratory disease and other systemic infections in cattle. One of the bacterium’s virulence factors is antigenic phase variation of its lipooligosaccharide (LOS). LOS antigenic variation may occur through variation in composition or structure of glycoses or their substitutions, such as phosphorylcholine (ChoP). However, the role of ChoP in the pathogenesis of H. somni disease has not been established. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…S. pneumoniae strains without ChoP-modified TA are unable to colonize the upper respiratory tract in mice and are less virulent in a murine sepsis model (49). ChoP expression in Histophilus somni has also been shown to increase colonization of its bovine host (50).…”
Section: Chop Affects Host Recognitionmentioning
confidence: 99%
“…S. pneumoniae strains without ChoP-modified TA are unable to colonize the upper respiratory tract in mice and are less virulent in a murine sepsis model (49). ChoP expression in Histophilus somni has also been shown to increase colonization of its bovine host (50).…”
Section: Chop Affects Host Recognitionmentioning
confidence: 99%
“…Three of the 40 re-isolates of TW07 had variation in the number of repeats and the frequency of variation was 7.5%. This high frequency may have resulted from immune selection since switching off ChoP expression enhanced the systematic survival of bacteria (Humphries & High, 2002;Elswaifi et al, 2012). Taken together, data presented here showed that Av.…”
Section: Discussionmentioning
confidence: 52%
“…Many mucosal pathogens, including H. influenzae, have evolved a mechanism for phase-variable (ON/OFF switching) expression of ChoP (Weiser et al, 1997;Warren & Jennings, 2003). It is proposed that switching ON expression of ChoP helps bacteria to colonize on the mucosal surface during the initial stage of infection, whereas switching OFF helps bacteria to escape serum killing mediated by C-reactive protein during systematic infection (Humphries & High, 2002;Elswaifi et al, 2012).…”
mentioning
confidence: 99%
“…The prechallenge with virus or dexamethasone was used to stress the animals and suppress the innate immune response. Without prior prechallenge, the animals become colonized but do not develop disease (13). These prechallenged stressed animals developed clinical symptoms of pneumonia.…”
mentioning
confidence: 99%
“…A postmortem examination revealed that the calves had various degrees of purulent bronchopneumonia with abscesses and multifocal purulent myocarditis. A more complete description of the pathology of each calf has been provided elsewhere (13). Normal respiratory tract bacteria, such as viridans group streptococci, were not isolated from the bronchoalveolar lavage fluid specimens, indicating that the H. somni isolates recovered from BAL fluid were not part of the normal upper respiratory tract flora.…”
mentioning
confidence: 99%